Current evidence for transurethral en bloc resection of non-muscle-invasive bladder cancer. Issue 4 (August 2014) - Kramer, Mario W.; Abdelkawi, Islam F.; Wolters, Mathias; Bach, Thorsten; Gross, Andreas J.; Nagele, Udo; Conort, Pierre; Merseburger, Axel S.; Kuczyk, Markus A.; Herrmann, Thomas R. W.
Abstract Introduction : Despite today's standard procedure for staging and treating non-muscle-invasive bladder cancer by transurethral resection via a wire loop (TURBT), several other publications have dealt with a different concept of en bloc resection of bladder tumors using different energy sources. Material and methods: MEDLINE and the Cochrane central register were searched for the following terms: en bloc, mucosectomy, laser, resection, ablation, Neodym, Holmium, Thulium, transitional cell carcinoma. Results: Fourteen research articles dealing with en bloc resection of non-muscle-invasive bladder cancer could be identified (modified resection loops: six, laser: six, waterjet hydrodissection: two). Conclusion: En bloc resection of bladder tumors >1 cm can be performed safely with very low complication rates independent of the power source. By using laser, complication rates might even be decreased, based on their good hemostatic effect and by avoiding the obturator nerve reflex. A further advantage seems to be accurate pathologic staging of en bloc tumors. Randomized controlled trials are still needed to support the assumed advantages of en bloc resection over the standard TURBT with regard to primary targets: First-time clearance of disease, accurate staging and recurrence rates.